Pengaruh Perkembangan E-Commerce, Modal Usaha, Pengetahuan Kewirausahaan, dan Penggunaan Sistem Informasi Akuntansi terhadap Pengambilan Keputusan Berwirausaha - Handayani, Delis; Rusmana, Oman; Warsidi, Warsidi (Jurnal Bisnis dan Pemasaran Digital, 2023)
Purpose: This study aims to determine and analyze the effect of the development of e-commerce, business capital, entrepreneurial knowledge, and the use of accounting information systems on entrepreneurial decision-making in Unsoed students. Methodology/approach: The type of data used is primary data using questionnaires. The sample size used in this study is 100. The sampling technique used in this study is purposive sampling based on certain criteria. Results/findings: The results of the study using SPSS version 25 show that: (1) The development of e-commerce has a positive effect on entrepreneurial decision-making, (2) Business capital has a positive effect on entrepreneurial decision-making, (3) Entrepreneurial knowledge does not have a positive effect on entrepreneurial decision making, (4) The use of accounting information systems has a positive effect on entrepreneurial decision making. Contribution: This research hopes that educational institutions can maximize programs related to entrepreneurship to increase students' ability to make entrepreneurial decisions, especially in terms of learning related to capital management of a business. Limitation: The factors that influence entrepreneurial decision-making in this research only consist of four variables, namely e-commerce development, business capital, entrepreneurial knowledge, and accounting information systems.